Journalism internship regulations of Spain’s public universities: between guaranteeism and deregulation - García-Borrego, Manuel; Gómez-Calderón, Bernardo; Farias, Pedro (Estudios sobre el Mensaje Periodístico, 2020)
This article analyses the regulation of internships of the 18 Spanish public universities where the Journalism degree was taught during the 2017-2018 academic year. The aim is to determine the way in which they regulate the aspects related to the professional routines of the students. A content analysis sheet with four variables —duration of the working day, economic endowment, compatibility regime with the studies and maximum period of development of the internships— is applied to the documents. Among other results, it is observed that only 27.8% of the universities establish remuneration for the internships, and although the majority sets a cap for the sessions (from 4 to 8 hours), 44.4% of the institutions let the companies be the ones to set the schedules of the students. Considering the payment-schedule axis, the universities in the sample are classified into four groups: guarantors, remunerative with limited regulation, non remunerative with limited regulation and deregulated.